Clematis erecta extract inhibits migration, invasion and induce apoptosis in breast cancer cells (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Migration and invasion of breast cancer cells to distant parts of the body is a hallmark of the disease. The disease becomes difficult to manage and treat with an increased invasion by cancer cells. Some drugs kill the cancer cells but causes general cytotoxicity but no drugs are known to inhibit the invasive potential of cancer cells. Previously, the natural components have been proven to exhibit anticancer and invasive potential. Clematis erecta L. (Ranunculaceae) Leaves infusion is traditionally used to treat syphilitic, cancerous and other foul ulcers. Moreover, methanolic extract and and ethyl acetate fraction exhibited significant analgesic and anti-inflammatory activity. The scientific literature still lacks support for the anticancer potential of C. erecta. Therefore, it was envisaged to investigate the anticancer activities of C. erecta aerial parts on breast cancer cells. The results obtained suggest that C. erecta has anti-invasive potential on triple-negative human breast cancer cells (MDA-MB-231). Three different extracts (chloroform, methanol and water) of aerial parts of C. erecta were evaluated for their effect on the growth and migration of human breast cancer cells MDA-MB-231. Interestingly, aqueous extract inhibits cell growth by more than 50% and also inhibits migration and invasion by 40 and 50%, respectively. DNA fragmentation of extract treated cells further suggested that C. erecta has the potential to kill cancer cells.